STUDENTS’ VIOLENCE AGAINST TEACHERS FROM THE PERSPECTIVE OF EDUCATIONAL PSYCHOLOGY AND TEACHERS’ PROFESSIONALISM - Moehamad Ridhwan (HOLISTICS, 2016)
Teachers are not expected to become only teachers. They must also be able to play their roles as educators. Here all challenges may come their way in establishing their career in which they are obliged to build their students’ character. To present the materials before the class may be quite a challange, but to make noble successful men out of the students is even more challenging. This task may be faced with violence from the students whose motivation of study is on the verge of being corrupted. This paper discusses in particular students’ psychological violence against teachers and how educational psychology comes in rescue to put the feather back on the teachers’ cap and maintain their professionalism.